2004
DOI: 10.1002/hep.1840400429
|View full text |Cite
|
Sign up to set email alerts
|

Aging does not reduce the hepatocyte proliferative response of mice to the primary mitogen TCPOBOP

Abstract: It has been shown that the magnitude of DNA synthesis and the time at which maximal DNA synthesis occurs after two-thirds partial hepatectomy (PH) is greatly reduced in the liver of aged rodents compared to young animals. This reduction could represent an intrinsic defect in proliferation or a more specialized change in the response to PH. We therefore evaluated the proliferative capacity of hepatocytes in aged animals, following treatment with primary liver mitogens. We show that treatment of 12-month-old CD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 25 publications
4
37
0
1
Order By: Relevance
“…In particular, the finding that aged hepatocytes thoroughly maintain their replicative capacity following mitogenic stimuli (Ledda- Columbano et al 2004) suggests that the depressed replicative response observed in aged rodent liver after PH results from lowered levels of extra-cellular factors, such as growth factors and/or hormones, rather than from intrinsic changes within the cell. In agreement with this, our present work found that the expression of several early changes, considered to be essential for liver regeneration (Yamada et al 1997;Cressman et al 1996;Michalopoulos and DeFrances 1997), is essentially similar in regenerating (young mouse) and non-regenerating (old mouse) liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the finding that aged hepatocytes thoroughly maintain their replicative capacity following mitogenic stimuli (Ledda- Columbano et al 2004) suggests that the depressed replicative response observed in aged rodent liver after PH results from lowered levels of extra-cellular factors, such as growth factors and/or hormones, rather than from intrinsic changes within the cell. In agreement with this, our present work found that the expression of several early changes, considered to be essential for liver regeneration (Yamada et al 1997;Cressman et al 1996;Michalopoulos and DeFrances 1997), is essentially similar in regenerating (young mouse) and non-regenerating (old mouse) liver.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis Total cell extracts were prepared from frozen livers as described previously (Ledda- Columbano et al 2004). For cyclin D1, D2, D3, and YAP, 100 mg of total extracts was prepared.…”
Section: Methodsmentioning
confidence: 99%
“…19,24 The probe for b-actin was prepared from total RNA using SuperScriptt IIIOne-Step RT-PCR System with Platinum Taq DNA Polymerase (Invitrogen, Carlsbad, CA, USA). Following PCR primers were used for b-actin: forward AGC CATGTACGTAGCCATCC and reverse AAGGGTGTAAAAC GCAGCTC.…”
Section: Northern Blotmentioning
confidence: 99%
“…Notably, it was shown that hepatocyte proliferation induced by TCPOBOP, a ligand of the constitutive androstane receptor (CAR), is age independent, suggesting that hepatocytes retain their proliferative capacity in old age despite impaired liver regeneration. 19 On the basis of these observations, the first aim of this study was to investigate whether pretreatment with xenobiotic mitogens, for example TCPOBOP, may allow the growth of the liver in conditions associated with a reduced regenerative capacity, such as the elderly. In particular, we address the question whether nuclear receptor-mediated signal transduction pathways could be capable of bypassing the growth-constrained environment of an aged liver, thus improving its proliferative capacity after 70% PH.…”
mentioning
confidence: 99%
“…CAR is able to regulate a set of genes common to the promotion of cellular growth. After a short treatment with TCPOBOP, the mice showed increased BrdU staining as well as rapid induction of cell cycle genes including cyclin D1 and cdk2 (Ledda-Columbano et al 2000;Ledda-Columbano et al 2004). Gadd45β, a gene involved in the repression of apoptosis, is also up-regulated in response to CAR activators (Columbano et al 2005).…”
Section: Cell Growthmentioning
confidence: 99%